Validation of the blood pressure measurement technology used in the Novacor Diasys 3 Plus (DIP-0001-00) upper-arm device for ambulatory blood pressure measurement, according to AAMI/ANSI/ISO 81060-2: 2013, ESH-IP 2010 and MEDDEV 2.7/1. Issue 6 (December 2020) - Atkins, Neil; Fania, Claudio; Palatini, Paolo
Abstract : Objective: The objective of this study was to determine the accuracy of the auscultatory and oscillometric blood pressure (BP) measurement technologies of the Novacor Diasys 3 Plus (model number DIP-0001-00) BP monitor, intended for ambulatory BP measurement when used with the recommended Standard Plus (ACC-0210-00), Large Plus (ACC-0211-00) and Paediatric Plus (ACC-0212-00) cuffs. Methods: The auscultatory measurement technology Novacor Diasys 3 Plus (model number DIP-0001-00) was evaluated according to the requirements of the AAMI/ANSI/ISO 81060-2:2013 standard, including an additional cardiac-stress study, a requirement for ambulatory BP measurement devices. It was also validated according to the requirements of the European Society of Hypertension International Protocol revision 2010. The oscillometric measurement technology was compared to that of the Novacor Diasys 3 (model number DIS-0001-00) according to the equivalence requirements of MEDDEV 2.7/1 rev 4. The protocol requirements for all three studies and the equivalence were followed precisely. Results: The Novacor Diasys 3 Plus (model number DIP-0001-00) fulfilled all of the requirements for a pass in each of the three studies of the auscultatory measurement technology. In the primary AAMI/ANSI/ISO 81060-2:2013 study, the criterion 1 errors were + 3.6 ± 2.7 mmHg for SBP and + 3.0 ± 2.7 mmHg for DBP. It was also proven to be equivalent to the Novacor Diasys 3 (model number DIS-0001-00) with respect to the oscillometric measurement technology Conclusion: The Novacor Diasys 3 Plus (model number DIP-0001-00), when used with the recommended cuffs, can be recommended for ambulatory BP measurement in the adult population. Abstract : Supplemental Digital Content is available in the text.